2009
DOI: 10.1159/000212672
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Lacunar Stroke: A Systematic Review

Abstract: Background: Endothelial dysfunction is thought to play an important role in the pathogenesis and progression of cerebral small-vessel disease in lacunar stroke patients. Methods: We systematically searched the literature (MEDLINE, EMBASE) for evidence of endothelial activation and dysfunction in lacunar stroke. The selected papers were assessed by a predefined checklist to estimate methodological and informative quality. The papers were categorized into subheadings concerning the different physiologic function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 103 publications
4
102
1
2
Order By: Relevance
“…Interestingly, the presence of MPs has also been reported to be positively associated with contrast-enhancing lesions on brain MRI in subjects with multiple sclerosis 35 and furthermore, endothelial dysfunction is thought to have an important role in the pathogenesis of cerebral small-vessel disease especially in those patients with concomitant silent lacunar infarcts and ischaemic WM lesions. 36 In line with this possible accelerated aging effect, the older member from the kindred B and one carrier of the PROM1 mutation in family A showed some memory disturbance and impairment in measures of executive functions in addition to small WM lesions. The remaining carriers in both families had average IQs and unimpaired performance on the other cognitive measures.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, the presence of MPs has also been reported to be positively associated with contrast-enhancing lesions on brain MRI in subjects with multiple sclerosis 35 and furthermore, endothelial dysfunction is thought to have an important role in the pathogenesis of cerebral small-vessel disease especially in those patients with concomitant silent lacunar infarcts and ischaemic WM lesions. 36 In line with this possible accelerated aging effect, the older member from the kindred B and one carrier of the PROM1 mutation in family A showed some memory disturbance and impairment in measures of executive functions in addition to small WM lesions. The remaining carriers in both families had average IQs and unimpaired performance on the other cognitive measures.…”
Section: Discussionmentioning
confidence: 86%
“…31 It is regarded that the activation of the cerebral microvascular endothelium might be the primary step in the pathogenesis of SLI, subsequently leading to increased permeability of the blood-brain barrier. 34,35 IR is also suggested to be related to endothelial dysfunction. Both IR and endothelial dysfunction are commonly observed in many cardiovascular diseases.…”
Section: Downloaded Frommentioning
confidence: 99%
“…11 A recent systematic review identified endothelial dysfunction in lacunar ischemic stroke but did not control for risk factor exposure or other stroke subtypes. 12 Therefore, it is unclear whether endothelial changes observed in patients with lacunar ischemic stroke might be specific to small vessel disease or simply reflect age, vascular risk factors, generalized (possibly coincidental) atheroma, or the effects of having a stroke. We performed a systematic review of all studies that assessed cerebral or peripheral vascular reactivity in patients with lacunar ischemic stroke.…”
mentioning
confidence: 99%